Combined effects of microplastics and warming enhance algal carbon and nitrogen storage. (15th April 2023) - Sun, Shan; Hu, Xiangang; Kang, Weilu; Yao, Mingqi
Highlights: MPs significantly alter algal carbon storage via growth rather than PSII system. MPs accelerate algal nitrogen uptake rate and nitrate reductase activity. MPs enhance algal carbon and nitrogen acquisition and utilization under warming. Fatty acid metabolism and TCA cycle contribute to the algal responses. Abstract: Algae dominate primary production in groundwater and oceans and play a critical role in global carbon dioxide fixation and climate change but are threatened by ongoing global warming events (such as heatwaves) and increasing microplastic (MP) pollution. However, whether and how ecologically important phytoplankton respond to the combined effects of warming and MPs remain poorly understood. We thus investigated the combined effects of these factors on carbon and nitrogen storage and the mechanisms underlying the alterations in the physiological performance of a model diatom, Phaeodactylum tricornutum, exposed to a warming stressor (25 °C compared with 21 °C) and polystyrene MP acclimation. Although warmer conditions decreased the cell viability, the diatoms subjected to the synergistic effects of MPs and warming showed significant increases in the growth rate (1.10-fold) and nitrogen uptake rate (1.26-fold). Metabolomics and transcriptomic analyses revealed that MPs and warming mainly promoted fatty acid metabolism, the urea cycle, glutamine and glutamate production, and the tricarboxylic acid (TCA) cycle due to an increased level of 2-oxoglutarate, which is the hub of carbon and nitrogen metabolism and accounts for the acquisition and utilization of carbon and nitrogen. Our findings emphasize the nonnegligible effects of MPs and HWs on the algal carbon and nitrogen cycles in waters.